Cardiomyocyte Specific Deletion of ADAR1 Causes Severe Cardiac Dysfunction and Increased Lethality - el Azzouzi, Hamid; Vilaça, Andreia P.; Feyen, Dries A. M.; Gommans, Willemijn M.; de Weger, Roel A.; Doevendans, Pieter A. F.; Sluijter, Joost P. G. (Frontiers in Cardiovascular Medicine, 2020)
Background: Adenosine deaminase acting on RNA 1 (ADAR1) is a double-stranded RNA-editing enzyme that is involved in several functions including the deamination of adenosine to inosine, RNA interference (RNAi) mechanisms and microRNA (miRNA) processing, rendering ADAR1 essential for life. Methods and Results: To investigate whether maintenance of ADAR1 expression is required for normal myocardial homeostasis, we bypassed the early embryonic lethality of ADAR1-null mice through the use of a tamoxifen-inducible Cre recombinase under the control of the cardiac-specific α-myosin heavy chain promoter (αMHC). Targeted ADAR1 deletion in adult mice caused a significant increase in lethality accompanied by severe ventricular remodeling and quick and spontaneous cardiac dysfunction, induction of stress markers and overall reduced expression of miRNAs. Administration of a selective inhibitor of the unfolded protein response (UPR) stress significantly blunted the deleterious effects and improved cardiac function thereby prolonging animal survival. In vitro restoring miR-199a-5p levels in cardiomyocytes lacking ADAR1 diminished UPR activation and concomitant apoptosis. Conclusions. Our findings demonstrate an essential role for ADAR1 in cardiomyocyte survival and maintenance of cardiac function through a mechanism that integrates ADAR1 dependent miRNA processing and the suppression of UPR stress.